Exploring readiness for the adoption of new molecular water quality tests: Insights from interviews with policy makers, laboratory managers and watershed managers. (April 2016) - Henrich, Natalie; Holmes, Bev; Isaac-Renton, Judith; Prystajecky, Natalie
Abstract: Adoption of molecular-based water quality tests has been limited despite their advantage over traditional culture-based tests. A better understanding of the factors affecting adoption of these tests is needed for effective implementation. The Consolidated Framework for Implementation Research (CFIR) was used to analyze interviews with policy makers, watershed managers and laboratory managers in British Columbia (BC), Canada about their perceptions of molecular water tests currently under development in order to assess readiness for adoption and identify factors that may impact implementation. Many of the CFIR constructs were addressed by study participants, thus confirming their validity in the water-testing context. Other constructs were not mentioned, which suggests that awareness about these constructs need to be increased to ensure that they are incorporated into implementation strategies. In general, there was much enthusiasm for the new tests, which were seen to provide valuable information that could enable improved management of watersheds and treatment of source water. However, prior to adopting the tests, stakeholders would require evidence supporting the tests' validity and reliability, would need to assess the complexity of introducing the tests into laboratories and water sampling processes, and would require support interpreting the test results. Even if all the aforementioned issues are satisfactorily addressed, the tests may not be adopted unless regulations and policies were changed to allow the use of these test results to inform decision making. The results support that implementation of new technologies, such as these water quality tests, need to address potential barriers that could hinder uptake despite the advantages of the new product. Highlights: Adoption of new molecular tests is impacted by technical and non-technical factors. Perceptions of new molecular water tests were interpreted with respect to adoption. Consolidated Framework for Implementation Research was used to contextualize results. Intervention ('test') characteristics were central to willingness to adopt. Non-technical characteristics need to be addressed to facilitate greater adoption.